Comparison of FSH Pre-treatment Versus Upfront hCG and FSH Regimens for Inducing Spermatogenesis in Congenital Hypogonadotropic Hypogonadism: A Pilot Study - Japleen Kaur; Nikhil Singhania; Umanath Adhikari; Richa Vatsa; Ujjwal Gorsi; Akash Bansal; Sanjay Bhadada; Nidhi Gupta; Anil Bhansali; Naresh Sachdeva; Aayushi Kaushal; Rama Walia (Indian Journal of Endocrinology and Metabolism)
Introduction: Appropriate gonadotropin therapy regimen for the induction of spermatogenesis in congenital Hypogonadotropic Hypogonadism (HH) patients is a matter of debate. Pre-treatment with hCG is discouraged, while the rationale for FSH pre-treatment is that it mimics minipuberty, thereby being expected to be better than upfront combined hCG and FSH therapy. Methods: A prospective RCT was conducted in the Department of Endocrinology of a tertiary centre. 24 azoospermic males between 17y and 40y of age with congenital HH were randomized into two groups. Group A (n = 12) received upfront combined hCG and FSH, while group B (n = 12) was given pre-treatment with FSH for 3 months, before addition of hCG. Results: Patients were followed up for a maximum duration of 18 months. Overall success rate was 91.3% (21/23). In group A, 100% (12/12) responded to treatment compared with 81.8% (9/11) in group B, with significantly lesser median (IQR) time to spermatogenesis of 10.5 (9–12) months in group A, compared to 15 (13.5–16.5) months in group B (P = 0.007). Maximum sperm concentration [median (IQR)] attained in group A and B was 30 (15.5–47) million/mL and 20 (7.5–34.5) million/mL, respectively (P = 0.292). Sonographic bi-testicular volume (median) increased to 8.05 (7.13–10.57) mL in group A and 9.2 (5.45–14) mL in group B. Conclusion: Both FSH pre-treatment and upfront combined hCG and FSH have a favourable outcome in initiating spermatogenesis in congenital HH, with the time to initiation of spermatogenesis favouring combined treatment.